The Gait of the Religious Harmony Forum (FKUB) in Making Harmonization Between Religions in Aceh Singkil Regency (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
This study aims to analyze the role of the Religious Harmony Forum (FKUB) in maintaining inter-religious harmony in Aceh Singkil Regency, including the direction of government policies in supporting the performance of FKUB to maximize its role as a religious institution. This research uses a sociological approach based on conflict and consensus theory. Researchers have conducted observations and interviews with FKUB administrators, religious leaders, and community leaders of different religions in the Aceh Singkil Regency to obtain data in the field. The findings in this study indicate several important points in the FKUB work program in Aceh Singkil Regency in maintaining inter-religious harmony, namely the implementation of inter-religious dialogue and stakeholders who have an interest in creating inter-religious harmony. Second, accommodate and channel aspirations by monitoring situations that can damage harmony. Third, in maintaining harmony, socialization of laws and regulations to religious communities as contained in several regulations, including Presidential Regulations, Ministerial Regulations, and Aceh Governor Regulation Number 25 of 2007. Fourth, community empowerment creates harmonization between religious communities by identifying and mapping problems and the potential for harmony. The role of FKUB in Aceh Singkil Regency in maintaining inter-religious harmony has not been able to run optimally due to the lack of budgetary support from the Regional Government. Nevertheless, there is a consensus among religious communities in Aceh Singkil Regency, supported by a strong base of social ties so that relations between religious communities can be maintained in harmony.